Effect of N-acetylcysteine on clozapine-induced sialorrhea in schizophrenic patients: a case series. (July 2020) - Uzun, Özcan; Bolu, Abdullah; Çelik, Cemil
Abstract : Clozapine is an atypical antipsychotic demonstrated to be superior in the treatment of refractory schizophrenia. Despite all this effectiveness, it has side effects that can be serious and bothersome. Sialorrhea is the most common adverse drug reaction that occurs during clozapine treatment. It is usually persistent, may impair the patient's quality of life and reduce treatment compliance. However, there is limited evidence to guide possible treatment strategies for sialorrhea. N-Acetylcysteine (NAC) is a powerful antioxidant. It acts directly as a scavenger of free radicals, in particular oxygen radicals. The antioxidant NAC also modulates glutamatergic, neurotrophic and inflammatory pathways. The first time we examined and reported the effect of NAC (1200–2400 mg/day) on clozapine-induced sialorrhea in a patient group of five patients. After four weeks of follow-up, the severity of sialorrhea decreased significantly with NAC augmentation. There were no significant side effects of NAC as measured by the UKU scale.